Current status and potential role of circular RNAs in neurological disorders. Issue 3 (6th June 2019) - Lu, Shanshan; Yang, Xue; Wang, Chudong; Chen, Siqi; Lu, Shuang; Yan, Weitao; Xiong, Kun; Liu, Fengxia; Yan, Jie
Abstract: Given the importance of non‐coding RNAs in modulating normal brain functions and their implications in the treatment of neurological disorders, non‐coding RNA‐based diagnostic and therapeutic strategies have shown great clinical potential. Circular RNAs (circRNAs) have emerged as potentially important players in this field. Recent studies have indicated that circRNAs might play vital roles in Alzheimer's disease, Parkinson's disease, ischemic brain injury, and neurotoxicity. However, the mechanisms of action of circRNAs have not been fully characterized. We aimed to review recent advances in circRNA research in the brain to provide new insights on the roles of circRNAs in neurological disorders. Abstract : Circular RNAs (circRNAs) are an emerging class of non‐coding RNAs which are enriched in the mammalian brain. Interaction between circRNAs and other non‐coding RNAs such as microRNAs (miRNAs) and long non‐coding RNAs (lncRNAs) is essential in modulating brain functions in rodent models. In this review we discuss the possible functional role of circRNA regulation within the brain and wish it may shed new light on the further studies of some neurodisorders (Alzheimer's disease, Parkinson's disease, ischemic brain injury, and neurotoxicity) in human.